1996
DOI: 10.1136/gut.38.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori increases proliferation of gastric epithelial cells.

Abstract: The direct and indirect effects of Helicobacter pylori on cell kinetics of gastric epithelial cell line AGS were investigated by flow cytometric analysis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 17 publications
5
83
0
Order By: Relevance
“…Fan et al reported a similar increase of Ki-67-positive cells in H. pylori-associated gastritis in humans. 19 In the fundic mucosa the BrdU labeling indices increased slightly but significantly at 4 weeks after inoculation, although the inflammatory cell infiltration remained almost negligible in the corpus. One could speculate that the inflammation in the pyloric mucosa might influence the cell turnover in the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al reported a similar increase of Ki-67-positive cells in H. pylori-associated gastritis in humans. 19 In the fundic mucosa the BrdU labeling indices increased slightly but significantly at 4 weeks after inoculation, although the inflammatory cell infiltration remained almost negligible in the corpus. One could speculate that the inflammation in the pyloric mucosa might influence the cell turnover in the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…9,22,32,33 The gastric epithelial cell proliferation results from both the direct effects of HP pathogenic factor, such as CagA, 34 and the indirect effects of inflammatory environment enriched with cytokines, such as TNF-α and IL-1β, induced by HP infection 24,35 that could activate the MAPK cascades. As expected, HP-infected WT mice showed elevated gastric epithelial proliferation in association with enhanced MAPK pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Based on the low degree of mucosal hyperplasia in OPN KO mice compared with WT mice after HP infection (Supplementary Figure S2), we performed IHC for Ki-67 on stomach tissues of HP-infected mice to investigate the impact Roles of osteopontin in H. pylori infection JW Park et al of the lack of OPN on gastric epithelial proliferation in response to HP infection. We found out that the number of Ki-67-positive gastric epithelial cells in HP-infected WT mice at 8 and 16 weeks after HP infection was significantly higher than that of uninfected WT mice (Figures 5a and b).…”
Section: Opn Deficiency Inhibits the Proliferation Of Gastricmentioning
confidence: 99%
“…H. pylori strains or rMIF was incubated with GECs for 24 h. Cells were lysed as described previously (32). Lysates were centrifuged at 14,000 ϫ g for 10 min at 4°C.…”
Section: P53 Phosphorylationmentioning
confidence: 99%